Pengaruh Ikan Lele (Clarias sp) terhadap Karakteristik Kerupuk Ikan Microwave sebagai Cemilan Sehat Tinggi Protein - Guttifera, Guttifera; Ratna Sari, Selly; Yesi, Desri; Arafah, Elmeizy; Cahya, Gemala (Publikasi Penelitian Terapan dan Kebijakan, 2024)
The purposed study is to produced crackers that can expand and produced a good surface appearance when cooked with a microwave oven. The research used a random design of factorial groups.The treatments were the formulations of catfish and tapioca (A) and levels microwave (B) (A1=1:2.5,A2=1.2:2.3,A3=1.4:2.1) and (B1=medium,B2=high). The Specified parameters include volume, texture and SEM (Scanning Electron Microscopy). The results showed that treatment of catfish and tapioca(A)formulations and power levels (B) had a real effect on the Volume and Texture of crackers embedded with microwave ovens. The crackers highest volume and the lowest texture are A3B2 (1.4:2.1, high) with a volume of 948.07% and a texture of 133.47 gf. Result of SEM (Scanning Electron Microscopy) analysis that samples with the highest fish formulation can produced a smoother surface appearance than other treatments.